Literasi Keuangan dan Preferensi Risiko terhadap Keputusan Investasi Cryptocurrency pada Generasi Milenial di Kota Jambi - Fitri Hamelinda; Setiawati, Rike; Wediawati, Besse (Jurnal Paradigma Ekonomika, 2024)
This study aims to describe the overview of financial literacy, risk preferences, and investment decisions, as well as analyze the influence of financial literacy and risk preferences on cryptocurrency investment decisions among the millennial generation in Jambi City. The research sample consisted of 95 respondents, selected using purposive sampling technique. Data collection in this study was conducted using a questionnaire with a Likert scale format. The collected data were then analyzed using Partial Least Square (PLS). The results of research indicate that the financial literacy and risk preferences of millennial cryptocurrency investors in Jambi City are at an excellent level. The very high financial literacy and risk preferences of these investors contribute positively to excellent cryptocurrency investment decision-making. Hypothesis testing results demonstrate that financial literacy and risk preferences have a positive and significant influence on cryptocurrency investment decisions. This study's findings have implications for efforts to enhance the rationality of cryptocurrency investment decisions to avoid undesirable losses, such as choosing types of crypto assets with not too high price volatility, or diversifying portfolios by combining crypto assets with conventional assets like stocks, bonds, or mutual funds.